ANTI-CYCLIC CITRULLINATED PEPTIDE ANTIBODIES AS A TOOL IN DIFFRENTIATING PATIENTS WITH RHEUMATOID ARTHRITIS FROM PATIENTS WITH CHRONIC HEPATITIS C INFECTION-ASSOCIATED POLYARTICULAR INVOLVEMENT - Ahmad, Ibrar; Taqweem, Amjad; Ali, Zafar; Alam, Intekhab; Mehboob, Amjad (Journal of Postgraduate Medical Institute, 2012)
Objective: To assess the utility of anti-cyclic citrullinated peptide (anti-CCP) antibodies in distinguishing between patients with rheumatoid arthritis (RA) and patients with polyarticular involvement associated with chronic hepatitis C virus (HCV) infection. Methodology: All the patients enrolled in this study were examined in the outpatient department of medicine unit at Lady Reading Hospital Peshawar from February to December 2010. Serum anti-CCP antibodies and rheumatoid factor (RF) were evaluated in 29 patients with RA, 13 patients with chronic HCV infection a associated with articular involvement and 35 patients with chronic HCV infection without any joint involvement. Results: Anti-CCP antibodies were detected in18 of 29 (62.1%) patients with RA, 7 of 13(53.8%) patients having HCV with RA like arthropathy but not in a single patient with chronic HCV infection with no articular involvement. Conversely, RF was detected in 25 of 29 (86.2%) patients with RA, 9 of 13 (69.2%) patients with HCV-related RA like arthropathy and 8 of 31 (22.9%) patients with HCV infection without joint involvement. Conclusion: This concludes that anti-CCP antibodies can be useful in discriminating patients with RA from patients with HCV-associated arthropathy.